Исследование методов повышения стойкости штампов горячего деформирования - Каргин, Б. С.; Каргин, С. Б. (НТУ "ХПИ", 2014)
Представлены результаты комплексных исследований по повышению стойкости штампов при горячей объёмной штамповке стали. Рассмотрены основные причины выхода штампов из строя, влияние азотирования, марки стали и типа технологической смазки (ТС) на стойкость штампов. Стойкость штампов в большой мере определяется структурой и свойствами поверхностных слоёв, которые претерпевают наиболее ощутимые изменения в процессе эксплуатации. Дано описание установки для автоматизированного нанесения ТС на гравюру штампа. На основании производственных исследований установлены эффективные методы повышения стойкости штампов при горячей объёмной штамповке.

The results of comprehensive research to improve the durability of dies in hot die forging steel. The main reasons for withdrawal dies down, the effect of nitriding steel grade and type of lubrication technology (TC) on the resistance of the dies. Persistence stamps largely determined by the structure and properties of surface layers that undergo the most significant changes in the operation. An effective means for neutralizing the adverse effects of the deformation are technological lubricant friction, which are introduced on the contact surface of the deformable metal tool. Persistence forging dies determines the cost of forgings. The description of the installation for automated application TC stamp engraving. Based on industrial studies establish effective methods of increasing the resistance dies in hot die forging.
Study of methods of increasing stamp resistance during hot deformation
Keywords: штампы; смазки; стойкость; прессы; установка; гравюры; графит; горячая объёмная штамповка; влияние азотирования; die; lubricant; durability; setting; engraving; graphite